Cyanine Conjugate‐Based Biomedical Imaging Probes. Issue 22 (1st October 2020) - Li, Yang; Zhou, Yiming; Yue, Xiuli; Dai, Zhifei
Abstract: Cyanine is a class of fluorescent dye with meritorious fluorescence properties and has motivated numerous researchers to explore its imaging capabilities by miscellaneous structural modification and functionalization strategies. The covalent conjugation with other functional molecules represents a distinctive design strategy and has shown immense potential in both basic and clinical research. This review article summarizes recent achievements in cyanine conjugate‐based probes for biomedical imaging. Particular attention is paid to the conjugation with targeting warheads and other contrast agents for targeted fluorescence imaging and multimodal imaging, respectively. Additionally, their clinical potential in cancer diagnostics is highlighted and some concurrent impediments for clinical translation are discussed. Abstract : The design, synthesis, and characterization of cyanine conjugate‐based biomedical imaging probes which are obtained from the covalent conjugation between cyanine fluorophores and other functional molecules, e.g., targeting warheads and other contrast agents for targeted fluorescence imaging and multimodal imaging, respectively. Additionally, their potential opportunities and pitfalls in clinical translation are analyzed from a diagnostic imaging perspective.